BAKTERI LEPTOSPIRA PATOC I MERUPAKAN STRAIN BAKTERI DALAM KELOMPOK NON PATOGEN YANG SERING DITEMUKAN PADA PENDERITA LEPTOSPIROSIS - Bina Ikawati; Dewi Marbawati (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2010)
Leptospirosis is one of zoonotic disease that needs serious attention from health practiciant and health programmer. This disease includes in the emerging infectious disease. Reseach from Loka Litbang P2B2 Banjarnegara in 2008 showed Leptospira of strain Patoc I (one of strain that include in non patogenic bacteria) found in 60,4% of 63 human blood sample that positive for Leptospira which Microscopic Aglutination Test (MAT). Literature studies on Leptospira bacteria strain Patoc I thus done about to know the reason why strain Patoc I usually found in Leptospirosis case, and wheter positive Patoc I in human spesimen indicates someone suffering from leptospirosis. Result showed Leptospira Sp strain Patoc I (Ames) or Patoc I (Paris) or Patoc I ATCC 23582 include in serovar Patoc, serogroup Semaranga, Genomospecies Leptospira biflexa, Genera Leptospira, family Leptospiraceae, ordo Spirochaetales, class Spirochaetes, Phylum Spirochaetes, Super Kingdom Bacteria. Patoc I usually showed cross reaction with many leptospira patogenic bacteria. Therefore Patoc I used as common indicator of Leptospirosis. Positive with Patoc I mostly indicates leptospirosis sufferer but probably from strain that not available in "batteray antigen test MAT" inlaboratory diagnosis. Research in laboratorium showed there was possibility of Patoc I genetic mutation.